Literary reflection of Status Society and Contract Society - Teixeira Gonçalves, Stephanie Gabrielle (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
In the 20th-century landscape, Isabel Paterson stands out, delineating fundamental principles of freedom, market, and minimal state. Simultaneously, Henry Maine contributes significantly to law and anthropology, outlining concepts of Status Society and Contract Society, relating both models to the evolution of humanity and its organizations. In this context, literature serves as an excellent medium to observe social issues, evident in the reflection of these notable intellectuals' theses. Starting with "Romeo and Juliet," there is a struggle for love, challenging expectations and matrimonial arrangements linked to noble lineages. "David Copperfield" unveils status and contract societies through the protagonist's maturation and struggles. Moving into the 20th century, Aldous Huxley's "Brave New World" envisions a dystopian future, exploring the dangers of conformity in a controlled, status-oriented society. In the 21st century, Harry Potter depicts the conflict between the two social molds.